Capital Adequacy Ratio And Its Influencing Factors On The Islamic Banking In Indonesia - Yolanda, Yolanda (IKONOMIKA, 2017)
Bank is one of the most decisive financial intermediary of a country's economy. Country that in the economies has healthy banking industries will have an impact on all the activity and stability of the economy. The purpose of this study is to investigate the determinants of the capital adequacy of Islamic banks in Indonesia by using panel data of eleven Islamic Banks from 2012 to 2016. This study uses secondary financial data that were analyzed using multiple linear regression model to the capital adequacy of banks (Capital Adequacy Ratio / CAR) as the dependent variable, and profitability (ROA, ROE, NIM) and Liquidity (FDR) as the independent variables. The findings of this study showedpositive correlation between the financial performance of capital adequacy and liquidity. As a result, this study provides more insight into the determinants that affect the capital adequacy of Islamic Banks in Indonesia.